A new classification for Lipocarpha and Volkiella as infrageneric taxa of Cyperus s.l. (Cypereae, Cyperoideae, Cyperaceae): insights from species tree reconstruction supplemented with morphological and floral developmental data - Bauters, Kenneth; Larridon, Isabel; Reynders, Marc; Asselman, Pieter; Vrijdaghs, Alexander; Muasya, A. Muthama; Simpson, David A. A.; Goetghebeur, Paul (Phytotaxa, 2014)
Recent molecular phylogenetic analyses showed that Lipocarpha and Volkiella are nested in a paraphyletic Cyperus s.s. and therefore should be viewed as part of a broadly circumscribed genus Cyperus (Cyperaceae). In this paper, molecular phylogenetic analyses of Lipocarpha and Volkiella based on nuclear ribosomal ETS1f and plastid rpl32-trnL and trnH-psbA markers are presented. Separate gene trees as well as a species tree were constructed. Results indicate a polyphyletic Lipocarpha s.l. consisting of a paraphyletic core Lipocarpha s.s in which the monotypic Volkiella is included, and a small non-related clade with species formerly placed in the genus Rikliella. Core Lipocarpha s.s. encompasses six clades, which can be distinguished based on morphological characters. Floral developmental data for Lipocarpha rehmannii (the type of Rikliella) confirms that this species is not a true Lipocarpha s.s. Based on our findings, Lipocarpha s.l. and Volkiella are here included in Cyperus subg. Cyperus. New names and combinations for Lipocarpha s.l. and Volkiella species and a new sectional classification for these species are proposed.